2015
DOI: 10.1530/joe-14-0709
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of somatostatin on insulin secretion is not mediated via the CNS

Abstract: The inhibitory effect of somatostatin (SST) on insulin secretion in vivo is attributed to a direct effect on pancreatic beta cells, but this is inconsistent with some in vitro results in which exogenous SST is ineffective in inhibiting secretion from isolated islets. We therefore investigated whether insulin secretion from the pancreatic islets may partly be regulated by an indirect effect of SST mediated via the CNS. Islet hormone secretion was assessed in vitro by perifusion and static incubations of isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Somatostatin is a powerful paracrine inhibitor of islet alpha and beta cells, which express different isoforms of the somatostatin receptor 10,11 . These receptors enable somatostatin-dependent suppression of glucagon and insulin release 12 , indirectly impacting glucose homeostasis 13,14 . Delta cells release somatostatin in response to acetylcholine 15 , glutamate 6 , urocortin3 (Ucn3) 16 , ghrelin 11 , and high glucose 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin is a powerful paracrine inhibitor of islet alpha and beta cells, which express different isoforms of the somatostatin receptor 10,11 . These receptors enable somatostatin-dependent suppression of glucagon and insulin release 12 , indirectly impacting glucose homeostasis 13,14 . Delta cells release somatostatin in response to acetylcholine 15 , glutamate 6 , urocortin3 (Ucn3) 16 , ghrelin 11 , and high glucose 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work in rat islets showed that DA inhibits SST secretion via its actions on D 2 -like receptors 92 . This raises the possibility that the DA synthesized by αand β-cells also locally activates δ-cell D2R to inhibit SST secretion and thus removes SSTmediated inhibition of insulin and glucagon release 32,91,[93][94][95][96][97][98] . Such paracrine DA signaling that involves α-, β-, and δ-cells may offer an additional dimension to our understanding of the intra-islet regulation of hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…n for each group is inside or at the top of the column level of estrogen, since estradiol deficiency, as seen in aged females, is known to decrease insulin sensitivity in the liver, skeletal muscle, and white adipose tissue; reduce GLUT4 expression in skeletal muscle and white adipose tissue; and stimulate food intake and gluconeogenesis (Foryst-Ludwig & Kintscher, 2010;Lu et al, 1998). The 18-month-old females in ad libitum conditions exhibited low plasma glucose, insulin, and triglyceride concentrations, indicating a possible decrease in intestinal absorption of glucose and triglycerides (Hahn et al, 1978;Hauge-Evans et al, 2015;Krejs et al, 1980;Wahren & Feling, 1976). The increased PRL concentration observed in older females may be due to the lack of response of hypothalamic tuberoinfundibular dopaminergic neurons or to a possible alteration of PRL receptors (Reymond, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the feeding animals, the highest glycemia in 3‐month‐old females could be a consequence of their low level of estrogen, since estradiol deficiency, as seen in aged females, is known to decrease insulin sensitivity in the liver, skeletal muscle, and white adipose tissue; reduce GLUT4 expression in skeletal muscle and white adipose tissue; and stimulate food intake and gluconeogenesis (Foryst‐Ludwig & Kintscher, 2010; Lu et al., 1998). The 18‐month‐old females in ad libitum conditions exhibited low plasma glucose, insulin, and triglyceride concentrations, indicating a possible decrease in intestinal absorption of glucose and triglycerides (Hahn et al., 1978; Hauge‐Evans et al., 2015; Krejs et al., 1980; Wahren & Feling, 1976).…”
Section: Discussionmentioning
confidence: 99%